2005
DOI: 10.4049/jimmunol.175.1.228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Natural Human Antibodies against a Nonhuman Sialic Acid That Metabolically Incorporates into Activated and Malignant Immune Cells

Abstract: Humans are genetically incapable of producing the mammalian sialic acid N-glycolylneuraminic acid (Neu5Gc), due to an inactivating mutation in the enzyme synthesizing it. Despite this, human cells and tissues appear capable of metabolically incorporating Neu5Gc from exogenous sources, including dietary red meat and dairy products. All normal humans studied are now shown to have circulating Abs against Neu5Gc, with marked differences in isotype levels. The question arises whether such Abs can adversely affect N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
146
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 43 publications
3
146
0
Order By: Relevance
“…Human sera contain naturally high levels of anti-N-glycolyl gangliosides antibodies even of IgG isotype (6,44), which only induce complement-mediated mechanism in leukemia cells (7). Our results suggest that this NGcGM3-mediated cell death seems to be a particular property of 14F7 variable region.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Human sera contain naturally high levels of anti-N-glycolyl gangliosides antibodies even of IgG isotype (6,44), which only induce complement-mediated mechanism in leukemia cells (7). Our results suggest that this NGcGM3-mediated cell death seems to be a particular property of 14F7 variable region.…”
Section: Discussionmentioning
confidence: 58%
“…N-glycolyl sialic acid differs by an additional oxygen atom to the Nacetyl moiety and is not detected in healthy human tissues due to a genetic deletion in the CMP-N-acetyl hydroxylase enzyme that catalyze the biosynthesis conversion of Nacetyl to N-glycolyl sialic acid (4). However, the N-glycolyl variant can be detected in some human tumors and fetal tissues (3,5), where is known to be immunogenic (6,7). Free N-glycolyl sialic acid can be metabolically incorporated into human carcinoma cells by fluid pinocytosis and lysosomal sialic acid transporter (8).…”
Section: Introductionmentioning
confidence: 99%
“…38 Meanwhile, healthy humans have significant and differing levels of circulating antiNeu5Gc antibodies. 38,39 Our current hypothesis is that chronic inflammation related to this antigen-antibody reaction could be facilitating both carcinogenesis and atherogenesis.…”
Section: Detection Of a Nonhuman Sialic Acid Neu5gc In Human Tissuesmentioning
confidence: 99%
“…This has been reported in both human tumors such as breast, colon, and skin cancers [10] and normal tissues including secretory epithelium and blood vessels [9]. Moreover, most humans have circulating anti-Neu5Gc antibodies [9,11] targeting this xenoglycan in serum [9,12]. Levels of anti-Neu5Gc antibodies vary among different individuals, but it has been suggested that chronic exposure to Neu5Gc and incorporation of this xenoglycan combined with circulating anti-Neu5Gc antibodies can promote chronic inflammatory states contributing to various diseases [14] including some of the diseases associated Hanganutziu-Deicher antibodies, which are reactive against Neu5Gc [13,14].…”
Section: Introductionmentioning
confidence: 99%